Analisis Optimasi Jalur Distribusi Menggunakan Pendekatan (Traveling Salesman Problem) untuk Meningkatkan Efisiensi Biaya Distribusi pada CV. Merdeka Pasuruan - Maulidi, M Agus; Sulistyowati, Enik; Riyana, Iis (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
CV. Merdeka is a company engaged in the construction of MWC NU REJOSO and MWC NU NGULING buildings. After seeing the demand for branch expansion, this growth can also be seen in an increase in distribution costs. The main goal is to find the route with the shortest total distance for analyzing this data using the Traveling Salesman Problem method. Based on the results and discussion, it is concluded that manual calculations provide optimal results, namely paths A to B is the shortest route that can be taken with a distance of 14.3 kilometers